Empirical Topical, Oral and Combination of Topical and Oral Antibiotics in Treatment of Chronic Otitis Media Mucosal Active: A Comparative Study - Khatri, Suman; Chettri, Shyam Thapa; Shah, Shankar Prasad; Shrestha, Sonika Dhari; Paneru, Manisha (Med Phoenix, 2024)
Introduction: Chronic otitis media is a common problem in Nepal. Due to overzealous use of expensive oral antibiotics there arise possibilities of severe systemic side effects. Such comparative study has not been done in the context of Nepal. This study will help to find the effective and better treatment modality for treatment of chronic otitis media. Materials and Methods: Among 300 patients above 14 years of age diagnosed with COM mucosal active were divided into 3 treatment groups randomly (100 in each group): Topical chloramphenicol (Group A), Oral Amoxicillin (Group B) and Combination of both oral Amoxicillin and topical chloramphenicol (Group C). Patients were followed up after two weeks and reassessment was done. Results: Out of 100 patients of each groups 77% following treatment with topical antibiotic, 80% following treatment with combination of oral and topical antibiotics and 69% following treatment with oral antibiotic only had resolution of ear discharge.This shows that there is no statistical significant difference in the outcome of treatment of patient with COM mucosal active with above three different antibiotic categories (p = 0.176). Conclusion: There is no significant difference in outcome of treatment of COM mucosal active disease with topical chloramphenicol ear drop or oral amoxicillin or combination of both topical chloramphenicol and oral amoxicillin.